Appendix

Graphs of the Parent Functions

Three graphs side-by-side. From left to right, graph of the identify function, square function, and square root function. All three graphs extend from -4 to 4 on each axis. Three graphs side-by-side. From left to right, graph of the cubic function, cube root function, and reciprocal function. All three graphs extend from -4 to 4 on each axis. Three graphs side-by-side. From left to right, graph of the absolute value function, exponential function, and natural logarithm function. All three graphs extend from -4 to 4 on each axis.

Graphs of the Trigonometric Functions

Three graphs of trigonometric functions side-by-side. From left to right, graph of the sine function, cosine function, and tangent function. Graphs of the sine and cosine functions extend from negative two pi to two pi on the x-axis and two to negative two on the y-axis. Graph of tangent extends from negative pi to pi on the x-axis and four to negative 4 on the y-axis. Three graphs of trigonometric functions side-by-side. From left to right, graph of the cosecant function, secant function, and cotangent function. Graphs of the cosecant function and secant function extend from negative two pi to two pi on the x-axis and ten to negative ten on the y-axis. Graph of cotangent extends from negative two pi to two pi on the x-axis and twenty-five to negative twenty-five on the y-axis. Three graphs of trigonometric functions side-by-side. From left to right, graph of the inverse sine function, inverse cosine function, and inverse tangent function. Graphs of the inverse sine and inverse tangent extend from negative pi over two to pi over two on the x-axis and pi over two to negative pi over two on the y-axis. Graph of inverse cosine extends from negative pi over two to pi on the x-axis and pi to negative pi over two on the y-axis. Three graphs of trigonometric functions side-by-side. From left to right, graph of the inverse cosecant function, inverse secant function, and inverse cotangent function.

Trigonometric Identities

Pythagorean Identities
{cos2t+sin2t=11+tan2t=sec2t1+cot2t=csc2t\begin{cases}{\cos }^{2}t+{\sin }^{2}t=1\\ 1+{\tan }^{2}t={\sec }^{2}t\\ 1+{\cot }^{2}t={\csc }^{2}t\end{cases}
Even-Odd Identities
{cos(t)=costsec(t)=sectsin(t)=sinttan(t)=tantcsc(t)=csctcot(t)=cott\begin{cases}\cos \left(-t\right)=\cos t\qquad \\ \sec \left(-t\right)=\sec t\qquad \\ \sin \left(-t\right)=-\sin t\qquad \\ \tan \left(-t\right)=-\tan t\qquad \\ \csc \left(-t\right)=-\csc t\qquad \\ \cot \left(-t\right)=-\cot t\qquad \end{cases}
Cofunction Identities
{cost=sin(π2t)sint=cos(π2t)tant=cot(π2t)cott=tan(π2t)sect=csc(π2t)csct=sec(π2t)\begin{cases}\cos t=\sin \left(\frac{\pi }{2}-t\right)\qquad \\ \sin t=\cos \left(\frac{\pi }{2}-t\right)\qquad \\ \tan t=\cot \left(\frac{\pi }{2}-t\right)\qquad \\ \cot t=\tan \left(\frac{\pi }{2}-t\right)\qquad \\ \sec t=\csc \left(\frac{\pi }{2}-t\right)\qquad \\ \csc t=\sec \left(\frac{\pi }{2}-t\right)\qquad \end{cases}
Fundamental Identities
{tant=sintcostsect=1costcsct=1sintcott=1tant=costsint\begin{cases}\tan t=\frac{\sin t}{\cos t}\qquad \\ \sec t=\frac{1}{\cos t}\qquad \\ \csc t=\frac{1}{\sin t}\qquad \\ \text{cot}t=\frac{1}{\text{tan}t}=\frac{\text{cos}t}{\text{sin}t}\qquad \end{cases}
Sum and Difference Identities
{cos(α+β)=cosαcosβsinαsinβcos(αβ)=cosαcosβ+sinαsinβsin(α+β)=sinαcosβ+cosαsinβsin(αβ)=sinαcosβcosαsinβtan(α+β)=tanα+tanβ1tanαtanβtan(αβ)=tanαtanβ1+tanαtanβ\begin{cases}\cos \left(\alpha +\beta \right)=\cos \alpha \cos \beta -\sin \alpha \sin \beta \qquad \\ \cos \left(\alpha -\beta \right)=\cos \alpha \cos \beta +\sin \alpha \sin \beta \qquad \\ \sin \left(\alpha +\beta \right)=\sin \alpha \cos \beta +\cos \alpha \sin \beta \qquad \\ \sin \left(\alpha -\beta \right)=\sin \alpha \cos \beta -\cos \alpha \sin \beta \qquad \\ \tan \left(\alpha +\beta \right)=\frac{\tan \alpha +\tan \beta }{1-\tan \alpha \tan \beta }\qquad \\ \tan \left(\alpha -\beta \right)=\frac{\tan \alpha -\tan \beta }{1+\tan \alpha \tan \beta }\qquad \end{cases}
Double-Angle Formulas
{sin(2θ)=2sinθcosθcos(2θ)=cos2θsin2θcos(2θ)=12sin2θcos(2θ)=2cos2θ1tan(2θ)=2tanθ1tan2θ\begin{cases}\sin \left(2\theta \right)=2\sin \theta \cos \theta \qquad \\ \cos \left(2\theta \right)={\cos }^{2}\theta -{\sin }^{2}\theta \qquad \\ \cos \left(2\theta \right)=1 - 2{\sin }^{2}\theta \qquad \\ \cos \left(2\theta \right)=2{\cos }^{2}\theta -1\qquad \\ \tan \left(2\theta \right)=\frac{2\tan \theta }{1-{\tan }^{2}\theta }\qquad \end{cases}
Half-Angle Formulas
{sinα2=±1cosα2cosα2=±1+cosα2tanα2=±1cosα1+cosαtanα2=sinα1+cosαtanα2=1cosαsinα\begin{cases}\sin \frac{\alpha }{2}=\pm \sqrt{\frac{1-\cos \alpha }{2}}\qquad \\ \cos \frac{\alpha }{2}=\pm \sqrt{\frac{1+\cos \alpha }{2}}\qquad \\ \tan \frac{\alpha }{2}=\pm \sqrt{\frac{1-\cos \alpha }{1+\cos \alpha }}\qquad \\ \tan \frac{\alpha }{2}=\frac{\sin \alpha }{1+\cos \alpha }\qquad \\ \tan \frac{\alpha }{2}=\frac{1-\cos \alpha }{\sin \alpha }\qquad \end{cases}
Reduction Formulas
{sin2θ=1cos(2θ)2cos2θ=1+cos(2θ)2tan2θ=1cos(2θ)1+cos(2θ)\begin{cases}{\sin }^{2}\theta =\frac{1-\cos \left(2\theta \right)}{2}\\ {\cos }^{2}\theta =\frac{1+\cos \left(2\theta \right)}{2}\\ {\tan }^{2}\theta =\frac{1-\cos \left(2\theta \right)}{1+\cos \left(2\theta \right)}\end{cases}
Product-to-Sum Formulas
{cosαcosβ=12[cos(αβ)+cos(α+β)]sinαcosβ=12[sin(α+β)+sin(αβ)]sinαsinβ=12[cos(αβ)cos(α+β)]cosαsinβ=12[sin(α+β)sin(αβ)]\begin{cases}\cos \alpha \cos \beta =\frac{1}{2}\left[\cos \left(\alpha -\beta \right)+\cos \left(\alpha +\beta \right)\right]\qquad \\ \sin \alpha \cos \beta =\frac{1}{2}\left[\sin \left(\alpha +\beta \right)+\sin \left(\alpha -\beta \right)\right]\qquad \\ \sin \alpha \sin \beta =\frac{1}{2}\left[\cos \left(\alpha -\beta \right)-\cos \left(\alpha +\beta \right)\right]\qquad \\ \cos \alpha \sin \beta =\frac{1}{2}\left[\sin \left(\alpha +\beta \right)-\sin \left(\alpha -\beta \right)\right]\qquad \end{cases}
Sum-to-Product Formulas
{sinα+sinβ=2sin(α+β2)cos(αβ2)sinαsinβ=2sin(αβ2)cos(α+β2)cosαcosβ=2sin(α+β2)sin(αβ2)cosα+cosβ=2cos(α+β2)cos(αβ2)\begin{cases}\sin \alpha +\sin \beta =2\sin \left(\frac{\alpha +\beta }{2}\right)\cos \left(\frac{\alpha -\beta }{2}\right)\qquad \\ \sin \alpha -\sin \beta =2\sin \left(\frac{\alpha -\beta }{2}\right)\cos \left(\frac{\alpha +\beta }{2}\right)\qquad \\ \cos \alpha -\cos \beta =-2\sin \left(\frac{\alpha +\beta }{2}\right)\sin \left(\frac{\alpha -\beta }{2}\right)\qquad \\ \cos \alpha +\cos \beta =2\cos \left(\frac{\alpha +\beta }{2}\right)\cos \left(\frac{\alpha -\beta }{2}\right)\qquad \end{cases}
Law of Sines
{sinαa=sinβb=sinγcasinα=bsinβ=csinγ\begin{cases}\frac{\sin \alpha }{a}=\frac{\sin \beta }{b}=\frac{\sin \gamma }{c}\qquad \\ \frac{a}{\sin \alpha }=\frac{b}{\sin \beta }=\frac{c}{\sin \gamma }\qquad \end{cases}
Law of Cosines
{a2=b2+c22bccosαb2=a2+c22accosβc2=a2+b22abcosγ\begin{cases}{a}^{2}={b}^{2}+{c}^{2}-2bc\cos \alpha \qquad \\ {b}^{2}={a}^{2}+{c}^{2}-2ac\cos \beta \qquad \\ {c}^{2}={a}^{2}+{b}^{2}-2ab\text{cos}\gamma \qquad \end{cases}

Licenses and Attributions

More Study Resources for You

The materials found on Course Hero are not endorsed, affiliated or sponsored by the authors of the above study guide

Show More